The Role of Cocoa Bean Trade Performance in Driving Regional Economic Growth - Intan Farida Khasanah (Ekraf: Jurnal Ekonomi Kreatif dan Inovatif Indonesia, 2025)
The cocoa trade plays a strategic role in the global economy and is one of Indonesia's leading commodities, contributing to regional development and farmer welfare. However, international price dynamics, productivity challenges, and value chain sustainability still create a gap between the potential and actual contribution of cocoa to regional economic growth, including in South Papua. This article aims to systematically examine the dynamics of Indonesia's cocoa trade, focusing on competitiveness, the role of the value chain, and its implications for sustainable development at the regional level. This study uses a systematic literature review approach, examining scientific publications, international agency reports, and official secondary data from the last five years. The results of the study show that although Indonesia has an important position in the world cocoa market, its competitiveness is still affected by limitations in cultivation technology, global price volatility, and the weak integration of small farmers in the international value chain. On the other hand, opportunities arise through the strengthening of farmer cooperatives, downstream product diversification, and the improvement of sustainable agricultural practices that can streng then regional economic resilience. The main contribution of this article lies in its conceptual synthesis linking cocoa trade with regional economic growth and sustainable development, while also offering a foundation for action.